The Oxford Handbook of the Psychology of Competition 2021
DOI: 10.1093/oxfordhb/9780190060800.013.24
|View full text |Cite
|
Sign up to set email alerts
|

Competition in Education

Abstract: In this chapter, the authors delineate how competition circulates through education. First, the authors show how competitive ideologies, values, and norms are transmitted from society to educational institutions, in particular ideologies and values such as meritocracy, the belief in a fair free market, and neoliberalism, as well as norms such as productivism and employability. Second, the authors review the competitive structures and climates within educational institutions that shape students’ values, goals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…The extent to which students perceive their classmates as competitive or cooperative, and their own orientations toward competitiveness and cooperativeness, are important predictors of social and learning outcomes (for reviews, see Butera et al, 2021; Elliot, 2020; Johnson & Johnson, 2021). Existing research on predictors of competitiveness and cooperativeness at school focus mainly on personal factors (e.g., social comparison tendencies), relational factors (e.g., relationship closeness), and task-based factors (e.g., incentive structures; for reviews see Garcia et al, 2013; Schneider et al, 2011).…”
Section: Competitiveness and Cooperativeness At Schoolmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent to which students perceive their classmates as competitive or cooperative, and their own orientations toward competitiveness and cooperativeness, are important predictors of social and learning outcomes (for reviews, see Butera et al, 2021; Elliot, 2020; Johnson & Johnson, 2021). Existing research on predictors of competitiveness and cooperativeness at school focus mainly on personal factors (e.g., social comparison tendencies), relational factors (e.g., relationship closeness), and task-based factors (e.g., incentive structures; for reviews see Garcia et al, 2013; Schneider et al, 2011).…”
Section: Competitiveness and Cooperativeness At Schoolmentioning
confidence: 99%
“…Competitiveness and cooperativeness shape how students navigate the social context of schools. On the one hand, competitiveness creates negative social interdependence in which the academic success of others is seen as an impediment to one’s own success; as such, it is not surprising that competitiveness often predicts undesirable peer interaction outcomes, such as intolerance for disagreements, information withholding, and tactical deception (for a review, see Butera et al, 2021). On the other hand, because cooperativeness creates positive social interdependence in which the academic success of others is seen as a catalyst of one’s own success, it is also not surprising that interventions designed to increase cooperativeness have been found to predict positive peer interaction outcomes, such as esprit de corps, social cohesiveness, and support for others (for a meta-analysis, see Roseth et al, 2008).…”
Section: Competitiveness and Cooperativeness At Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a reduction of the competitive norms at school could alleviate the pervasive effects of backlash and prove beneficial for minority and stigmatized social groups, such as students with special educational needs. In this perspective, neoliberal policies' growing impact on education in Western European nations could be a significant barrier in this regard (Butera et al, 2021;De Beco, 2018). Because this ideology aims to encourage competition and increase employment through the development of skills and the appreciation of merit, schools are expected to participate in the improvement of competitiveness and help produce economic growth by fostering students' abilities and skills in that direction 3 .…”
Section: Moving Toward Greater Inclusionmentioning
confidence: 99%
“…According to Dubet (2006), school meritocracy constitutes both a social ideal and a way of rewarding individuals, as most people consider merit as a fair basis for rewarding efforts and talent when comparing individuals. Research in the sociology of education and social psychology has demonstrated that this ideology is a cornerstone of many educational systems and is particularly prevalent in occidental countries (Butera et al, 2021). Thus, school meritocracy can be operationalized as an ideology that justifies inequalities, and as a principle of justice that promotes a social model based a supposed “equality of opportunity” (Pavie et al, 2021; Pratto et al, 1994).…”
Section: Defining School Meritocracymentioning
confidence: 99%